Discovering The Effect of Online Consumer Reviews Towards Purchasing Decisions - Deliza Rahmadona Andera; Ina Ratnasari (International Journal of Education, Information Technology, and Others, 2023)
This research aims to know, explain and analyze the impact of online consumer review on the use of one of the e-learning platform in Indonesia. The research was conducted using a descriptive and verification method, sample in this research is the user of an e-learning provider in Indonesia who decided to use the product mostly based on online consumer review. Data collected using online questionnaires, data analysis conducted with regression analysis. The results of the research on the level of significance 5% found that based on the research that has been done, the conclusion that can be taken the online consumer review is positive and significant effect on the user decision of the e-learning provider, this is evidenced by the value of T count > T table (4.561 > 1.938), the significance is smaller than 0.05 (0.00 < 0.05). The online consumer review has a positive and significant effect on the decision of using this provider, as evidenced by the value F count > F table ( 21,636 > 2.36).